Penyuluhan Dan Pelaksanaan Prenatal Yoga Untuk Mengurangi Nyeri Punggung Pada Ibu Hamil TM III DI BPM Kota Bengkulu Tahun 2023 - Rismayani; Lety Arlenty; Nurul Maulani (Gayaku Publisher, 2023)
One of the complaints during pregnancy includes back pain that occurs in TM III pregnant women. One effort to reduce back pain complaints is prenatal yoga. Prenatal ypga can stretch the muscles around the spine and provide flexibility, so to overcome this discomfort, non-conventional therapy is needed, one of which is prenatal yoga. Yoga practice is currently widely used to improve the health of pregnant women, because the possibility of drugs side effects on the fetus and pregnant mother is very minimal. This service activity aims to increase knowledge and involvement of pregnant women in doing prenatal yoga to improve health. This activity is carried out in several stages, namely establishing relationships, providing proposals and determining the activity schedule, then, there will be an evaluation of the process of community serv ice activities, namely a question and answer session. Counseling on this activity is carried out using lecture, discussion and practice methods.